2005
DOI: 10.1088/1742-6596/5/1/017
|View full text |Cite
|
Sign up to set email alerts
|

Clan structure analysis and new physics signals inppcollisions at LHC

Abstract: Abstract. The study of possible new physics signals in global event properties in pp collisions in full phase space and in rapidity intervals accessible at LHC is presented. The main characteristic is the presence of an elbow structure in final charged particle MD's in addition to the shoulder observed at lower c.m. energies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In anticipation for the upcoming operation of LHC in 2008, multiparticle production has again become one of major discussion in high energy physics recently [1,2]. In the previous studies, negative binomial distribution (NBD), which Giovannini has shown as a solution to the stochastic branching equation [3] that governs the dynamics of multiparticle production, is usually used to describe the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…In anticipation for the upcoming operation of LHC in 2008, multiparticle production has again become one of major discussion in high energy physics recently [1,2]. In the previous studies, negative binomial distribution (NBD), which Giovannini has shown as a solution to the stochastic branching equation [3] that governs the dynamics of multiparticle production, is usually used to describe the experimental data.…”
Section: Introductionmentioning
confidence: 99%